Computer Crimes: The Ecuador Case - Ponce Tubay, Manuel Alexander (2024)
The present study aims to analyze the different types of internet attacks and how they are classified as crimes in the Ecuadorian Comprehensive Organic Penal Code. The research relies on a qualitative method with a descriptive analysis of the collected literature, which involved a thorough review of documents, books, journal articles, and websites about various cybercrimes that occur in Ecuador. The focus is on the vulnerability of users and services on the web, with an emphasis on cyberattacks, and how computer crimes are classified in Ecuadorian laws. In conclusion, it is established that Ecuador lacks a legislative framework to support the security of citizens' information. Additionally, there are shortcomings in relation to the classification of computer crimes, as well as the recognition of different activities that contribute to these crimes and the absence of promotion of secure protocols in response to user vulnerability.